Transformational Leadership as the Basis of Public Services In Indonesia - Bustomi, Thomas; Aliah, Nurul; Kasmita, Maya; Asmar, Asmar; Syarifuddin, Syarifuddin (Jurnal Pallangga Praja (JPP), 2024)
The role of leadership, particularly transformational leadership, is increasingly recognized as fundamental to organizational effectiveness. This qualitative research delves into the significance of transformational leadership as the cornerstone of public service provision in Indonesia. The background stems from the evolving governance structures and the acknowledged influence of leadership styles on service delivery outcomes. The study aims to explore the correlation between transformational leadership and public service efficacy, focusing on how leaders inspire, motivate, and empower their subordinates to enhance organizational performance and service quality. Employing qualitative methods, data collection involves interviews, focus group discussions, and document analysis with key stakeholders such as government officials, public service providers, and citizens. Thematic analysis is utilized to discern patterns and themes regarding the impact of transformational leadership on public service outcomes. The findings underscore the significant influence of transformational leadership on organizational culture, employee morale, and service excellence. Leaders exhibiting transformational traits foster innovation, collaboration, and citizen engagement, thereby bolstering the overall effectiveness of public service delivery. This research contributes to understanding leadership dynamics within the Indonesian public sector and emphasizes the pivotal role of transformational leadership in driving positive organizational change and enhancing public service provision.